Public Involvement and Consultation for the Development of Nuclear Energy in Malaysia: (Penyertaan dan Konsultasi Masyarakat dalam Pembangunan Tenaga Nuklear di Malaysia) (Kanun: Jurnal Undang-undang Malaysia, 2020)
Nuclear waste is a global issue for which the best solution concerning storage, transportation and disposal has yet to be found. This matter is further complicated by catastrophes such as those that have occurred at Three Mile Island in the USA, Chernobyl in Russia and the nuclear plant meltdown incident at Fukushima, Japan. These have sparked concerns about the sustainable methods of nuclear waste management in ensuring the safety and health of the population, and the impact on the environment in the vicinity of nuclear plants or nuclear waste storage centers. In Malaysia, efforts towards nuclear power generation are in the beginning stages. Radioactive waste at the Lynas, Gebeng Industrial Estate in Pahang has sparked issues among the locals. This has brought about an outcry of "Not in My Backyard", which in turn has a political, economic and social impact. This paper aims at exploring the nature of the problems and the legal issues involved, as well as attempting to recommend possible solutions for public engagement and continuous communication with the community. The final aim is public acceptance and the commitment of the government to be more transparent and effective when it comes to control and enforcement.Keywords: nuclear waste, nuclear, radioactive, management, international law, consultation, public participation, environmental law, licencing